Intrusion of Kuroshio Helps to Diminish Coastal Hypoxia in the Coast of Northern South China Sea - Lui, Hon-Kit; Chen, Chen-Tung Arthur; Hou, Wei-Ping; Liau, Jian-Ming; Chou, Wen-Chen; Wang, You-Lin; Wu, Chau-Ron; Lee, Jay; Hsin, Yi-Chia; Choi, Yan-Yu (Frontiers in Marine Science, 2020)
Since half century ago, the number and area of dead zones (dissolved oxygen (DO) < 2 mg L-1 or 30% saturation) in the coastal oceans have increased dramatically. As is widely recognized the increased terrestrial nutrient and organic matter inputs are the two main factors causing the eutrophication of many coastal oceans. Here we show with decadal observed time series data from stations off the Pearl River Estuary and in the northern South China Sea (nSCS) that a strong intrusion into the nSCS of the West Philippine Sea (WPS) seawater in the form of Kuroshio branch occurred during the warm phase of the Pacific Decadal Oscillation (PDO) around 2003–2004 and 2015–2016 (also a strong El Niño event). Consequently, the DO concentration increased but NO3- and PO43- concentrations decreased in the subsurface layers of the nSCS. The WPS seawater was observed to reach the hypoxic area off the Pearl River Estuary in 2003–2004. Likely, due to the oxygen supply carried by the Kuroshio, little hypoxia developed. Yet, anoxic condition developed in the cold phase of PDO or strong La Niña years with weak Kuroshio intrusions.